Early Childhood Education in Post-War Liberia: Challenges, Opportunities, and Implications for Sustainable Development - Forkpah, Eric; Boholano, Helen (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa Tanah Datar Sumatera Barat, 2024)
This study delves into the landscape of early childhood education within Liberia's post-war Suakoko District, precisely examining challenges and untapped opportunities. Information was systematically gathered from educators, parents, and community members through structured interviews designed around key themes. Despite facing formidable constraints, including insufficient resources, early childhood education emerges as a pivotal force capable of fostering social cohesion, nurturing human capital, and fortifying community resilience in Suakoko. The results underscore the profound importance of early childhood education as a transformative catalyst for sustainable development in post-conflict environments, with a specific focus on Liberia's Suakoko District. In navigating the aftermath of war, the study illuminates the potential impact of investing in the foundational years of education, shedding light on the enduring benefits that extend beyond the individual to contribute to the broader fabric of societal progress and stability.